Application of Data Mining in Industry in the Transition Era to Industry 4.0: Review - Sahraoui, Khaoula; Samia Aitouche; Aksa, Karima (The Twelfth International Conference on Information, Process, and Knowledge Management (eKNOW 2020), 2020)
The era of Industry 4.0 has already begun, however, several improvements should be achieved concerning this revolution. Data mining is one of the modest and efficient tools. Based on a specific query entered in Scopus, related to Industry 4.0, data mining (DM) and logistics, selected documents were studied and analyzed. A brief background of Industry 4.0 and DM are presented. A generic analysis showed that the attentiveness for the cited subject area by countries, universities, authors and especially companies and manufacturers increased through the years. Content analysis reveals that the improvement in quality of the technologies used in manufacturing was noticed, concluding that DM would give Industry 4.0 a leap forward, yet research is dealing with several challenges.